STRATEGIES FOR MANAGING TIME EFFECTIVELY IN ACADEMIC SETTINGS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides practical strategies for managing time effectively in academic settings. It emphasizes the importance of prioritizing tasks, using tools like the Eisenhower Matrix to identify what needs immediate attention, and setting SMART goals for clear, actionable objectives. The piece advocates for creating detailed schedules, breaking tasks into smaller chunks, and avoiding multitasking to enhance focus and productivity. Additionally, the article highlights the role of digital tools and apps in tracking progress, as well as the significance of self-care and learning to say no to avoid burnout. Finally, it encourages regular review and adjustment of time management strategies to ensure they remain effective. The article serves as a comprehensive guide for students looking to improve their time management skills for academic success.